2000
DOI: 10.1002/etc.5620190818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sensitivity and specificity of two crustacean biochemical biomarkers

Abstract: Abstract-Biochemical biomarkers are increasingly used for environmental assessment. Although the emphasis has been on vertebrate biomarkers, invertebrates biomarkers have been developed as well. This study evaluated the usefulness of biomarker responses of freshwater invertebrates by comparing the sensitivity and specificity of endpoints at three levels of biological organization: biochemical, physiological, and individual. The study focused on the epibenthic amphipod Gammarus pulex L., and the end points were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 42 publications
3
64
1
2
Order By: Relevance
“…For the crustacean group, a large number of publications refer to a concentration-dependent inhibition of ChE with OP and carbamate pesticides (Supplemental Data, Table S1). This has been documented for Daphnia magna [30][31][32][33][34], Gammarus pulex [4], Hyalella azteca [35], and Procambarus clarkii [36] with several OPs and carbamates. These observations are in accordance with the expectations based on the mode of action of carbamates and OP pesticides.…”
Section: Cholinesterasementioning
confidence: 95%
See 1 more Smart Citation
“…For the crustacean group, a large number of publications refer to a concentration-dependent inhibition of ChE with OP and carbamate pesticides (Supplemental Data, Table S1). This has been documented for Daphnia magna [30][31][32][33][34], Gammarus pulex [4], Hyalella azteca [35], and Procambarus clarkii [36] with several OPs and carbamates. These observations are in accordance with the expectations based on the mode of action of carbamates and OP pesticides.…”
Section: Cholinesterasementioning
confidence: 95%
“…The biomarker approach, adopted from medical toxicology, is based on the assumption that low concentrations of a toxicant will cause a biochemical response within an organism before detrimental effects are observed at higher levels of biological organization. However, its use has presented difficulties for interpretation, namely, to what extent a biomarker response can be reliably linked to an environmental effect of ecological relevance [4,5]. Generally, biomarkers can be defined as a pathway-or a receptor-specific endpoint that can be considered a measurable stressor-induced variation in biochemical, physiological, and morphological status of an organism [6].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of ChE activity has been proposed as an effective tool for monitoring the exposure of organisms to organophosphorus and carbamate pesticides, whereas induction of GST can be suggestive of exposure to organochlorine compounds. McLoughiln et al [40] have used these biomarkers, together with mortality and feeding inhibition, to assess the potential risk of major classes of toxic chemicals (i.e. metals, surfactants, organochlorine, organophosphorus, and pyrethroid pesticides) to amphipod Gammarus pulex.…”
Section: Early Warning In the Field: Biomarkersmentioning
confidence: 99%
“…Feeding depression has been found as a sensitive endpoint for measuring the response of the organism to chemical exposure [21]. Food is the basic requirement for growth and other physiological functions of the body [22].…”
Section: Effects Of Pesticides and Antibiotics In Penaeid Shrimpmentioning
confidence: 99%
“…Food is the basic requirement for growth and other physiological functions of the body [22]. Feeding rate has been proposed in several studies as a sensitive indicator of toxic stress in both freshwater and marine species [23][24][25]. García de la Parra et al [20] observed that, in whiteleg shrimp (Litopenaeus vannamei) exposed to sublethal concentrations of 0.66, 0.83, 1.01, 1.18, and 1.35 mg/L methamidophos for 24 h under the experimental conditions of 258C, 32 ppt, 12:12 h light:dark photoperiod, the feeding rate did not show significant differences among treatments.…”
Section: Effects Of Pesticides and Antibiotics In Penaeid Shrimpmentioning
confidence: 99%